Gejala Akut Abdomen Terselubung pada Pasien Gagal Jantung Akut: Identifikasi Awal dengan Ultrasonografi Darurat: Laporan Kasus - Nugroho, Hari Adityo; Prasetyadjati, Ari; Johan, Willy (Cermin Dunia Kedokteran, 2025)
Background: The use of USG (ultrasonography) in the ED (emergency department) has grown rapidly to aid decisions on management. Case: A 71-year-old woman with a history of heart disease, in shock condition, fever for 2 days, and diarrhea was referred with diagnosis of cardiogenic shock. On physical examination there were no signs of an acute abdomen, with suspicion of sepsis. Chest x-ray and urine examination did not find signs of infection. During treatment, consciousness and vital signs worsened; abdominal ultrasound showed signs of acute abdomen which was confirmed by 2-position abdominal x-ray. Discussion: In this case, the final diagnosis was septic shock with cardiogenic shock due to secondary peritonitis due to perforated viscous organ and electrolyte imbalance (mild hyponatremia and hypochloremia), altered mental state and geriatric problem. Surgery was not possible due to the patient’s condition. The patient succumbed on the 2nd day of treatment. Conclusion: Bedside ultrasound examination helps to establish an earlier diagnosis in patients especially with atypical symptoms and may be the key to providing better medical decisions in the ED.